Multi-dose vials versus single-dose vials for vaccination: perspectives from lower-middle income countries - Saurav Basu; Ruchir Rustagi (Taylor & Francis Group, 2022)
The choice of the vaccine packaging type either as single- or multi-dose vial is a crucial determinant of vaccine coverage. The experience of vaccination strategies in lower-middle-income countries suggests that multi-dose vaccine vials translate into greater economic-logistic advantages due to lower packaging and storage costs with significant environmental benefits accrued from reduced medical waste generation. However, the use of multi-dose vials is associated with a theoretical risk of contamination particularly from human error. Moreover, the overall economic advantage of multi-dose vials is contingent on the reduction of the extent of vaccine wastage associated with their use. Robust data collection for monitoring of vaccine wastage rates and adverse effects following immunization is therefore needed to understand the extent of economic benefit and risks involved with multi-dose vial use.